Awareness and Perception of Salivary Diagnostics of Dental Students and Faculty: A Pilot Study - Matthew Cosaert; Nathan Hold; Filmon Kifle; Jordan Mar; Steven Powell; Udochukwu Oyoyo; So Ran Kwon (Journal of the California Dental Association)
Background The purpose was to determine the perception of the use of salivary diagnostics amongst dental students and faculty and assess if this perception changed after personally experiencing salivary diagnostic testing.Materials and Methods Participants completed a pretest survey on salivary diagnostic testing perception. Participants supplied a saliva sample and samples were analyzed for detection of pathogens associated with periodontal disease. Test results were distributed to respective participants with a standardized verbal explanation. Participants completed a posttest survey. A paired sample t-test was conducted to compare the differences in perception between pre- and post-survey results.Results A total of 50 participants completed the study; among the participants, 92% were dental students and 8% were dental faculty. The distribution of familiarity with the concept of salivary diagnostics indicated that most participants were unfamiliar with it. Perception towards salivary diagnostics increased after first-hand experience with salivary diagnostic testing. The overall satisfaction on the experience of salivary diagnostics was positive. Furthermore, linear regression analysis showed that age had a significant negative effect on overall satisfaction, p = 0.008Conclusions The overall satisfaction on the experience of salivary diagnostics as a screening tool in dentistry was positive. Furthermore, dental students and faculty’s perceptions of salivary diagnostics changed after first-hand experience with salivary diagnostic testing.Practical Implications Exposure to personal experiences with salivary diagnostics significantly improved the perception on salivary diagnostics, indicating the need for increased curricular emphasis on this topic at dental schools.